Key Approaches to Defining the Concept of «Adult Learning» in the Countries of Сentral and Еastern Еurope - Boiarska-Khomenko, Anna (Pedagogical Discourse, 2017)
The article emphasizes the relevance of the terminology analysis in the field of continuous education and, in particular, the scientific substantiation of the concept of «adult learning». It has been determined that the nomenclature of adult learning issues in modern Ukrainian pedagogical literature is not clear enough, it does not include a number of aspects and approaches to this concept. It has been specified that in the national state normative and legal acts the term «adult learning» is not disclosed, there is practically no explanation of the peculiarities of adult learning as part of the concept of continuing education in Ukraine. The author of the article has analyzed the scientific and pedagogical substantiation of the term «adult learning», outlined the theoretical foundations and approaches to the definition of adult learning in the pedagogical theory and normative and legal documents of the countries of Central and Eastern Europe. In particular, the literature and documents of such European countries as Austria, Bulgaria, Germany, Poland, Romania, the Czech Republic and Ukraine have been studied. Different approaches to understanding the concept of «adult learning», in particular social, economic, personal and cultural one, are shown. The peculiarities of the identification of the concepts of adult learning, continuous education, lifelong education on the example of some European countries have been considered. Several meanings of the term «adult learning» have been analyzed: as a quantitative and qualitative independent component of the continuous education system; as a form of action that includes teaching, learning, leadership, professional and consulting activities, as well as educational and library activities; as a theory and a scientific discipline. The essence of the concept of formal, nonformal and informal adult education in the Common European normative legal acts (Glossary of the European Higher Education Area, General Assembly Resolution, Council Resolution of the European Union, Glossary of the European Union Program «Erasmus+», Conclusions of the Executive Commission on Education and Culture of the European Union) has been revealed. Based on the study of these documents, the functions of adult learning have been defined: the level of formal education completion; obtaining knowledge and skills in the new branch; knowledge updating in a particular field; comprehensive personal development and participation in balanced and independent social, economic and cultural life of society.